Immunohistochemical Expression of Epithelial-Mesenchymal Transition Markers in Early Gastric Cancer: Cancer Tissue versus Noncancer Tissue - Hee Jae Jung; Su Jin Hong; Shin Hee Kim (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims Epithelial-mesenchymal transition (EMT) is a developmental process, wherein the epithelial cells show reduced intercellular adhesions and acquire migratory fibroblastic properties. EMT is associated with downregulation in epithelial marker expression, abnormal translocation of E-cadherin, and upregulation in mesenchymal marker expression. Here, we investigated the immunohistochemical (IHC) expression of EMT markers in early gastric cancer (EGC) between cancer and noncancer tissues. Methods Tissue samples were prospectively obtained from 19 patients with EGC that underwent endoscopic submucosal dissection (ESD). We compared the expression level of transforming growth factor (TGF)-β, vascular endothelial growth factor (VEGF), E-cadherin, α-smooth muscle actin (α-SMA), and vimentin between cancer and noncancer tissues using IHC. Among the 19 patients, 15 patients had follow-up biopsy at 3 months after ESD for EGC. Results Cancer tissues presented higher values of EMT mesenchymal markers (α-SMA/vimentin/TGF-β/VEGF) than the noncancerous tissues (p<0.05) that were significantly low after ESD (p<0.05). No significant correlation was reported for tumor location and initial Helicobacter pylori infection. Conclusions The mesenchymal expression of EMT markers was higher in the cancerous tissues than in the noncancer tissues.